2022
DOI: 10.1002/cjoc.202200160
|View full text |Cite
|
Sign up to set email alerts
|

Ultralong Organic Phosphorescence Modulation of Aromatic Carbonyls and Multi‐Component Systems

Abstract: Aromatic carbonyls have evoked sustained attention in the field of room-temperature phosphorescence (RTP). The introduction of carbonyl groups is a general way to achieve RTP for their effective intersystem crossing (ISC) by improving spin-orbit coupling (SOC). With further molecular design and processing strategies, aromatic carbonyls materials with multi-functional and high efficiency ultralong organic phosphorescence (UOP) can be obtained. This review summarizes the mechanism of aromatic carbonyls with UOP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 129 publications
0
5
0
Order By: Relevance
“…However, low triplet energy also results in a large energy gap between the lowest singlet and triplet states (Δ E ST ), preventing efficient intersystem crossing (ISC). [ 42‐46 ] Embedding the ladder guests into a crystalline small molecule renders RTP emission with high performance. The host matrix provides rigid environment to restrict movement and serves as a bridge to facilitate ISC between the singlet and triplet states of the guests.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…However, low triplet energy also results in a large energy gap between the lowest singlet and triplet states (Δ E ST ), preventing efficient intersystem crossing (ISC). [ 42‐46 ] Embedding the ladder guests into a crystalline small molecule renders RTP emission with high performance. The host matrix provides rigid environment to restrict movement and serves as a bridge to facilitate ISC between the singlet and triplet states of the guests.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[ 14‐16 ] Generally, organic luminogens in a single component seldom exhibit persistent phosphorescence at ambient conditions due to their intrinsic spin‐forbidden intersystem crossing (ISC) from the lowest single state (S 1 ) to the triplet state (T n ) as well as their ultrafast triplet exciton deactivation. Tremendous endeavors, including the introduction of heteroatoms, [ 17‐18 ] heavy halogen atoms, [ 3,19 ] sulfonyl groups, [ 14 ] keto groups, [ 20‐23 ] and multimers, [ 24‐26 ] have been made to enhance the ISC efficiency and populate triplet excitons, successfully turn on the persistent phosphorescence of pure organic luminogens. Nevertheless, most of them turn on RTP relying on highly ordered crystalline structures.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…Dopant‐matrix design strategies developed by us and others have shown that organic matrices can modulate the triplet excited state properties of luminescent dopants for the fabrication of high‐performance organic RTP materials. [ 14,22‐38 ] Glassy or crystalline matrices have been found to provide rigid microenvironments for luminescent dopants to inhibit nonradiative decay of dopants’ triplet excited states. [ 22‐23 ] Hydrogen bonding between matrices and dopants can also significantly reduce nonradiative decay of the triplet excited states of luminescent dopants.…”
Section: Background and Originality Contentmentioning
confidence: 99%